Agroforestry systems: Biodiversity, carbon stocks and contribution to rural livelihood - Ghimire, P.; Bolakhe, S. (Journal of Agriculture and Forestry University, 2020)
Agroforestry is an integrated land use system that can directly enhance agro-biodiversity and contribute to the conservation of landscape biodiversity, and also to the rural livelihoods. Considering this fact, a study was done in Bhimphedi Rural Municipality of Makawanpur district to assess farm tree diversity, carbon stock, and their contribution to the rural livelihood. The inventory for estimating above and below ground biomass of the farm trees was done using stratified random sampling. Forest biomass was analyzed by using standard allometric models to estimate the carbon content. Shannon Wiener Diversity Index was used to assess the farm tree diversity. A total of 66 households were randomly selected for socio-economic survey. Direct field observation, key informant interview, structured questionnaire survey, and group discussions were performed to assess the contribution of farm trees on rural livelihoods. The findings revealed three major agroforestry systems viz: silvi-pasture, home garden, and agri-silviculture systems were under practice in the study area. Silvi-pasture system was found as a good agroforestry system in terms of having higher species richness, tree diversity, and relatively higher amount of carbon stock per unit area (16.66 t/ha), followed by home garden (10.32 t/ha). The findings also revealed that agroforestry systems contributed 24.06% (NRs. 7580 per household/year), and 20.25% (NRs. 5365 per household/year) to the income from agriculture and livestock, respectively. Hence, it has been evident that agroforestry systems can be a potential strategy to conserve biodiversity and to improve the livelihoods of local people with the greater contribution of silvi-pasture system in an integrated tree-livestock dominating farming system of the rural areas in Nepal.